New Modalities of 3D Pluripotent Stem Cell-Based Assays in Cardiovascular Toxicity - Orsolits, Barbara; Kovács, Zsófia; Kriston-Vizi, János; Merkely, Béla; Földes, Gábor (Frontiers in Pharmacology, 2021)
The substantial progress of the human induced pluripotent stem cell (hiPSC) technologies over the last decade has provided us with new opportunities for cardiovascular drug discovery, regenerative medicine, and disease modelling. The combination of hiPSC with 3D culture techniques offers numerous advantages for generating and studying physiological and pathophysiological cardiac models. Cells grown in 3D can overcome many limitations of 2D cell cultures and animal models. Furthermore, it enables the investigation in an architecturally appropriate, complex cellular environment in vitro. Yet, generation and study of cardiac organoids - which may contain versatile cardiovascular cell types differentiated from hiPSC - remain a challenge. The large-scale and high-throughput applications require accurate and standardised models with highly automated processes in culturing, imaging and data collection. Besides the compound spatial structure of organoids, their biological processes also possess different temporal dynamics which require other methods and technologies to detect them. In this review, we summarise the possibilities and challenges of acquiring relevant information from 3D cardiovascular models. We focus on the opportunities during different time-scale processes in dynamic pharmacological experiments and discuss the putative steps toward one-size-fits-all assays.